2021
DOI: 10.35848/1347-4065/abdf23
|View full text |Cite
|
Sign up to set email alerts
|

Fine structural and photoluminescence properties of Mg2Si nanosheet bundles rooted on Si substrates

Abstract: Creating vertically aligned 2D nanostructures is a promising approach to achieving advanced electronic and optoelectronic materials. In this study, Mg2Si nanosheet bundles were synthesized by Ca atom extraction from CaSi2 microwalls grown on Si substrates via thermal annealing in a MgCl2/Mg mixed vapor. The nanosheet bundle structure was modified to compound nanosheet bundles from previously reported Si nanosheet bundles. The observed Mg2Si nanosheets consist of thin Mg2Si layers, and well-defined fine-scale M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 55 publications
0
6
0
Order By: Relevance
“…Furthermore, the incorporation of Mg into Si, Ge, and Si 1−x Ge x was investigated. The synthesis of Mg 2 Si nanosheet was reported via extraction of Ca atom from CaSi 2 , followed by the incorporation of Mg into Si substrates via thermal annealing in a MgCl 2 /Mg mixed vapor at 600 °C for 2 h. 6) The Mg 2 Si 1−x Ge x was produced under the given experimental conditions of the Si-Ge-Mg system.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, the incorporation of Mg into Si, Ge, and Si 1−x Ge x was investigated. The synthesis of Mg 2 Si nanosheet was reported via extraction of Ca atom from CaSi 2 , followed by the incorporation of Mg into Si substrates via thermal annealing in a MgCl 2 /Mg mixed vapor at 600 °C for 2 h. 6) The Mg 2 Si 1−x Ge x was produced under the given experimental conditions of the Si-Ge-Mg system.…”
Section: Resultsmentioning
confidence: 99%
“…4,5) In addition, several stoichiometric compounds, such as Mg 2 Si, MnSi 1.7 , Mg 2 SiO 4 nanosheet bundles, and CaF 2 nanostructures were synthesized. [6][7][8][9] Furthermore, the crystalline solid-solutions enable variations in stoichiometry of the continuum, which correspond to the variations in structural and physicochemical properties, and offer an opportunity to produce and finely tune the desired properties.…”
Section: Introductionmentioning
confidence: 99%
“…8 8), as compared to the Si-based nanosheets synthesized at higher annealing temperatures (600 °C-750 °C). 29,49) The formation of Mg compounds in the Si-based nanosheets was confirmed by XRD and Raman measurements. In contrast, the formation of Mg compounds was not confirmed in the Ge-based nanosheets prepared in this study by XRD or Raman spectroscopy.…”
Section: Ge S 2hcl Gmentioning
confidence: 86%
“…26) The Mg 2 Si nanosheet bundles were synthesized by annealing in MgCl 2 /Mg mixed vapor. 27) An additional Mg source was required to form homogeneous single-phase Mg 2 Si nanosheet bundles.…”
Section: Discussionmentioning
confidence: 99%
“…49) The morphology evaluation indicated that the thickness of MnSi 1.7 sheets is thinner than that of Mg 2 Si nanosheet bundles. 27) A small void space was formed between the nanosheets owing to the reduction in volume caused by the Ca atom extraction. An additional small volume reduction as V MnSi1.7 /V Si = 0.96 was caused by the incorporation of Mn atoms into the Si nanosheets.…”
Section: Discussionmentioning
confidence: 99%